Developing critical thinking through Socratic Questioning: An Action Research Study - Husniah, Sahamid (Australian International Academic Centre, Australia, 2016)
An action research study was conducted among 24 Form 4 level Malaysian students, aged 16. The duration of the study was five months and constituted 16 one-hour literature lessons (short stories from the secondary level Malaysian English Language Upper Secondary Level school syllabus). This paper describes my experience as a teacher-as-researcher to assist students to respond to teacher questions through Paul’s (1993) model of Socratic Questioning which claims to develop students’ critical thinking. Data was collected through researcher’s field notes, students’ writing tasks and student interviews which were analysed after each cycle of the action research study. Changes and adaptations were consequently made based on the data collected and upon teacher reflection to improve practice. The results of this study indicate that repeated practice of Socratic Questioning had a positive effect on student responses and writing tasks. Some of the factors affecting students’ performance included students’ language proficiency, weak reading ability and students’ anxiety towards the questioning method. These issues had to be addressed and dealt with, before Socratic Questioning could be properly implemented in the classroom